2021
DOI: 10.3390/brainsci11060765
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Repetitive Transcranial Magnetic Stimulation (rTMS) on Theory of Mind and Executive Function in Major Depressive Disorder and Its Correlation with Brain-Derived Neurotrophic Factor (BDNF): A Randomized, Double-Blind, Sham-Controlled Trial

Abstract: Background: Studies have implicated hypofrontality in the pathogenesis of impaired theory of mind (ToM) and executive function (EF) in major depressive disorder (MDD). These symptoms are usually resistant to treatment. Repetitive transcranial magnetic stimulation (rTMS) has been shown to reverse hypofrontality. Moreover, BDNF is an effective biomarker of antidepressant effects, but there have been very few studies on the correlation between BDNF and rTMS. We aimed to evaluate the efficacy of 20 sessions of a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…TSP can restore CP-induced phosphorylate CREB in mice. The results suggest that the BDNF/TRKB/CREB pathway may be involved in the protective effect of TSP to ameliorate CP-induced neuronal apoptosis and neurogenesis, which is consistent with previous papers that the recovery of BDNF function may be the basis of antidepressant therapy ( 53 ). Further exploration is needed to expound whether TSP crosses the BBB and the mechanism of its CP-induced anxiety- and depression-like behavior effects.…”
Section: Discussionsupporting
confidence: 92%
“…TSP can restore CP-induced phosphorylate CREB in mice. The results suggest that the BDNF/TRKB/CREB pathway may be involved in the protective effect of TSP to ameliorate CP-induced neuronal apoptosis and neurogenesis, which is consistent with previous papers that the recovery of BDNF function may be the basis of antidepressant therapy ( 53 ). Further exploration is needed to expound whether TSP crosses the BBB and the mechanism of its CP-induced anxiety- and depression-like behavior effects.…”
Section: Discussionsupporting
confidence: 92%
“…We included 110 studies, encompassing a total of 4820 participants . The majority of participants were male (2959 [61.4%] compared with 1861 females [38.6%]), and the mean (SD) age was 43 (8.8) years.…”
Section: Resultsmentioning
confidence: 99%
“…The details of all retained studies and the overall results for dose equivalents are reported in eTable 1 in Supplement 1 and the Table, respectively. Overall, considering the important heterogeneity found for borderline disorder and autism spectrum disorder, we included 33 studies on schizophrenia, 43 on mood disorders, 18 on OCD, 4 on posttraumatic stress disorder (PTSD), and 11 on substance use disorder (SUD) . We also included 32 studies on treatment-resistant depression .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis have shown that rTMS treatment targeting the prefrontal cortex in patients with MDD may moderately enhance cognitive function in set-shifting ability, visual scanning, and psychomotor speed ( 21 ). Tong et al showed that rTMS might improve executive function in patients with MDD ( 22 ). Repetitive transcranial magnetic stimulation is considered promising and valuable for improving cognitive dysfunction in TRD ( 23 ).…”
Section: Introductionmentioning
confidence: 99%